Model Edukasi Seksual Incest pada Anak Berbasis Parenting Islam di Madarasah Ibtidaiyah Kota Bengkulu - Karni, Asniti; Zumrotus Sa’adah, Diana; Rahmalia, Putri (UIN Fatmawati Sukarno Bengkulu, 2024)
Child sexual abuse has become an epidemic that continues to worsen, the increasing number of cases has caused deep anxiety among parents, schools, and the community. This study aims to design a parent education model that integrates Islamic parenting principles as a preventive measure against cases of child sexual abuse. This study will examine how Islamic values can be taught effectively to protect children from sexual abuse by their own family members. The sample of this study was all MI students in Bengkulu City, totaling 105 students. This study adopted a development research approach to develop an effective program. Data collection was carried out by distributing questionnaires to students, parents, and teachers, as well as through observation, interview, and documentation study techniques. This questionnaire was compiled based on three domains, namely cognitive, affective, and psychomotor, using a Likert scale. The results of the study showed that the use of the human skeleton as a learning medium was proven to be effective in helping students understand material about the human body. Teachers felt more comfortable, but students' practical skills still needed to be improved. Open communication about sexuality between parents and children is still a challenge. The SBFC model has emerged as a promising solution in preventing and addressing incest cases through strengthening family and school relationships.